Carisma e Poder: Categorias elementares da retórica da igreja universal do reino de Deus - RODRIGUES, Jadir Goncalves (2011)
In this research, we proposed to study the expansion and consolidation process of the Universal Church of the Kingdom of God (UCKG) in the troubled social context in Brazil during the period between 1977 and 2007, analyzing the abstract and concrete elements that enabled the phenomenal growth of this religious institution in a scenario of crisis and profound changes in the Brazilian social universe. We aimed at discussing the several steps in the process of consolidation of UCKG, investigating how, in an environment of religious dispute, the doctrinal discourse of the UCKG leaders was capable of drawing up a new model of religiosity and, simultaneously, enabled this religious denomination to constitute an impressive capital asset. The dissemination of a religious doctrine essentially based on the triad prosperity, exorcism, and divine healing presented excellent results in the Brazilian social context in the period under study. Furthermore, it forged concrete circumstances that enabled UCKG leaders to dispute power positions in the Brazilian social structure. During this process, the mass media ownership was of fundamental importance for UCKG leaders and so was the rhetorically orchestrated power, understood as the effective access property and control of mechanisms of influence, convincement, and social manipulation. Thanks to a scenario of generalized crisis, UCKG leaders were able to disseminate their doctrine, mainly due to the use of mechanisms to access and control properties, wielding their power over part of the society. With this thesis we intend to contribute towards the academic discussion that deals with the expansion and consolidation, in the Brazilian religious and patrimonial universe, of the brand UCKG, emphasizing its capacity to create spaces both in the religious field and in the business environment.